Media Use and Gratification Sought by the Public during the Coronavirus Outbreak in Indonesia: A National Survey - Mira Rochyadi-Reetz; Eni Maryani; Anna Agustina (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2020)
The recent coronavirus outbreak is without a doubt a global crisis event that has affected almost all nations of the world. This study aims to contribute to crisis communication research from the audience perspective in Indonesia by presenting the public’s media use and gratification sought during the coronavirus outbreak based on a representative national mobile survey with 1,100 respondents. Results show that the majority of Indonesians intensively use (1) private television, (2-4) websites and social media accounts of actors providing information on the crisis and (5) public television to get information regarding the pandemic. The findings indicate that other types of media such as radio and local television are used to a much lower extent. Results also show that there are two media-use gratifications sought during the crisis: (1) information and direction gratification sought and (2) entertainment and comparison gratification sought. Sociodemographic factors such as gender, age and education level demonstrate some significant influence on public media use and the gratification sought during the coronavirus outbreak. Surprisingly, entertainment and comparison sought are demonstrated as having a higher effect on the increasing use of mass media, social media and messenger apps during the crisis event than the information and direction gratification sought.